2015
DOI: 10.1097/jim.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Eating Speed at Breakfast on Appetite Hormone Responses and Daily Food Consumption

Abstract: Eating speed at breakfast did not affect postprandial ghrelin, GLP-1, PYY, hunger, and fullness values or daily energy and macronutrient intake. Desire to eat was lower at 60 minutes in the slow versus fast eating condition, but this result could not be explained by the changes in meal-related hormones measured in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…In contrast, Shah M et al reported that eating speed could not be explained by the changes in meal-related hormones. In their study, eating breakfast slowly (30 min) and quickly (10 min) did not affect postprandial gut hormone responses such as ghrelin, glucagon-like-peptide-1 (GLP-1), PYY, nor hunger and daily food consumption [26]. In the present study, IAUC for glucose of breakfast and lunch demonstrated no difference, possibly because the secretion of the incretin hormones might not be affected by eating speed in the daytime.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast, Shah M et al reported that eating speed could not be explained by the changes in meal-related hormones. In their study, eating breakfast slowly (30 min) and quickly (10 min) did not affect postprandial gut hormone responses such as ghrelin, glucagon-like-peptide-1 (GLP-1), PYY, nor hunger and daily food consumption [26]. In the present study, IAUC for glucose of breakfast and lunch demonstrated no difference, possibly because the secretion of the incretin hormones might not be affected by eating speed in the daytime.…”
Section: Discussioncontrasting
confidence: 57%
“…In a fixed-meal study, meal duration (30 versus 10 min) had no effect on appetite and hunger hormones or feelings of hunger or fullness after the meal. 127 Intakes throughout the rest of the day also were not different between eating speed conditions. Given that high heterogeneity between studies has been reported 126 and that no studies have assessed long-term Table 3.…”
Section: Discussionmentioning
confidence: 87%
“…Accordingly, a randomized cross-over study examined the effect of eating speed at breakfast on appetite hormone response, total daily intake, and subjective appetite perceived by the participants. Desire to eat at 60 min was significantly lower in the slow than in the fast eaters, but no association was found between breakfast eating speed and peripheral appetite hormone concentrations (ghrelin, GLP-1, PYY), hunger, fullness, or daily energy intake [37]. Another cross-over clinical trial conducted on normal-weight and overweight participants compared the effect of consuming the same meal ad libitum, but at different speeds, and assessed the weight and energy content of the food as well as perceived hunger and fullness at different times using visual analog scales.…”
Section: Discussionmentioning
confidence: 99%